Improving mathematical literacy: How does PBL affect the students’ performance? - Andini, Fadhila; Siregar, Machrani Adi Putri (Bulletin of Applied Mathematics and Mathematics Education, 2024)
This research is motivated by the many problems that often arise during classroom learning, especially mathematics. The aim of this research is to find out how students' abilities and problems are described in learning mathematics regarding relationships and functions taught using problem-based learning models and conventional learning models. With a post-test-only control group design, this research is a quasi-experimental research. The population in this study were all class VIII students at Bahagia Medan Private Middle School. Cluster random sampling was used to select 36 participants from each of two classes (control class and experimental class). This research instrument is a test with five questions. Based on the results of data analysis, the sig value was obtained. (2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that Problem Based Learning and conventional learning produce significantly different levels of mathematical literacy. The practical implication of this research is that educational practitioners, especially mathematics teachers at the junior high school level, can utilize these findings to improve their teaching. PBL can be used as a basis for designing more innovative and student-centered learning units, which can help students develop a deeper understanding of mathematical concepts and improve their ability to solve problems. Adequate support and training for teachers in implementing PBL is also important to ensure its successful implementation in the classroom.